VoIP hacks - Wallingford, Ted (O'Reilly, 2005)
Voice over Internet Protocol (VoIP) is gaining a lot of attention these days, as more companies and individuals switch from standard telephone service to phone service via the Internet. The reason is simple: A single network to carry voice and data is easier to scale, maintain, and administer. As an added bonus, it's also cheaper, because VoIP is free of the endless government regulations and tariffs imposed upon phone companies. VoIP is simply overflowing with hack potential, and VoIP Hacks is the practical guide from O'Reilly that presents these possibilities to you. It provides dozens of hands-on projects for building a VoIP network, showing you how to tweak and customize a multitude of exciting things to get the job done. Along the way, you'll also learn which standards and practices work best for your particular environment. Among the quick and clever solutions showcased in the book are those for: gauging VoIP readiness on an enterprise network using SIP, H.323, and other signaling specifications providing low-layer security in a VoIP environment employing IP hardphones, analog telephone adapters, and softPBX servers dealing with and avoiding the most common VoIP deployment mistakes In reality, VoIP Hacks contains only a small subset of VoIP knowledge-enough to serve as an introduction to the world of VoIP and teach you how to use it to save money, be more productive, or just impress your friends. If you love to tinker and optimize, this is the one technology, and the one book, you must investigate.